Improving Students Learning Outcomes through Implementing Make-a-Match Cooperative Model on Human Respiratory System Topic - Nufitasari, Nufitasari; Mardiyyaningsih, Asriah Nurdini; Tenriawaru, Andi Besse (Jurnal Pijar Mipa, 2024)
The make-a-match cooperative model is a learning model in which the teacher prepares cards containing questions or problems and prepares answer cards, and then students look for their card pairs. The direct involvement of learners in the learning process will lead to the formation of knowledge and skills that will improve learning outcomes. Implementing the make-a-match learning model is more directed to the game because each learner can search for answers or pairs of question cards obtained more freely and actively. Science learning at MTs Negeri I Kubu Raya still needs to provide a pleasant learning experience. Students' interest in participating in science learning still needs to be higher. It impacts unsatisfactory learning outcomes, as seen from the many student learning outcomes below the Minimum Completion Criteria set by the school. This condition requires science learning that can encourage students to be directly involved and play an active role during learning so that the learning process can run well. The cooperative model of the match type is predicted to increase collaborative learning and student participation in a fun learning situation wrapped in a game situation. This model requires students to find question-answer pairs through interaction with friends in one class. This study aims to measure the improvement of students' learning outcomes in class VIII B MTs Negeri I Kubu Raya on the material of the human respiratory system using the make-a-match cooperative model. The research was conducted over two cycles, and each cycle consisted of two meetings with four stages: planning, action, observation, and reflection. The research subjects totalled 32 people, all of whom were female. Data collection techniques include observation and tests using observation sheet instruments and learning outcomes test questions that have been previously validated. The improvement in learning outcomes focused on this research is the improvement of cognitive learning outcomes. The data was presented as a percentage score of observation of the learning process of the match cooperative model and classical completeness. The results showed that the achievement of implementing the learning process using the make-a-match cooperative model was 100% in both the first and second cycles. The average learning outcome of students on human respiratory system material in the first cycle was 79.68 and increased to 84.84 in the second cycle. Activities carried out by students also increased in each cycle. The increase leads to the activeness or participation of students during learning. Based on the study's results, it can be concluded that learning using the make-a-match cooperative model can improve learning outcomes and students' activeness.